The sea of monsters - Riordan, Rick (New York : Disney/Hyperion Books, 2008)
Demi-god Percy Jackson and his friends must journey into the Sea of Monsters to save their camp. But first Percy will discover a secret that makes him wonder whether being claimed as Poseidon's son is an honor or a cruel joke.
Keywords: Mythology, Greek -- Fiction; Fantasy fiction